Development of process flow sheet for syngas production from sorption enhanced steam gasification of palm kernel shell - Shahbaz, M. (Italian Association of Chemical Engineering - AIDIC, 2017)
This study discusses the production of synthesis gas from palm kernel shell via sorption enhanced steam gasification. A flowsheet model that has been presented incorporates the reaction kinetics and mass balance of syngas production process. It was assumed that the reactions involved in steam gasification of biomass with carbon dioxide adsorption, including gasification, methanation, methane reforming, water gas shift, boudouard and carbonation reaction. A parametric study has been performed to investigate the effect of temperature, steam/biomass ratio and sorbent/biomass ratio on the product gas compositions and heating values of the final product. It was concluded that the hydrogen content in product gas increased in the temperature range of 650-750 °C. The effect of sorbent/biomass ratio was investigated in the range of 0.5-1, which showed an increasing trend for hydrogen production while the CO2 contents reduced in the final product gas. The mass balance has also been presented for each of the equipment in flow sheet developed for synthesis gas production. Copyright © 2017, AIDIC Servizi S.r.l.